Enhancing Information Literacy Skills through Think Talk Write Online Learning Model - Rachman, Reza Saeful; Damaianti, Vismaia Sabariah; Mulyati, Yeti; Sastromiharjo, Andoyo (FKIP Universitas Lampung, 2022)
Enhancing Information Literacy Skills through the Think Talk Write Online Learning Model. Objectives: This study aims to analyze the effectiveness of the Think Talk Write (TTW) learning model which is carried out online on students' information literacy skills at the tertiary level. Method: This study used a quasi-experimental method with a pretest-posttest non-equivalent control group design. The research was conducted on students of Indonesia University of Education social studies program with a total of 250 people consisting of 125 people in the experimental group and 125 people in the control group. Findings: The results showed that Think, talk, and write activities have an impact on providing students with opportunities to read, process, and utilize various information. Conclusion: The conclusion is that the application of the TTW learning model has a higher effectiveness than the application of conventional learning models in terms of achieving student information literacy. Keywords: information literacy, think talk write, online learning.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202225